If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(4x) + 5 = 7 Remove parenthesis around (4x) ln * 4x + 5 = 7 Reorder the terms for easier multiplication: 4ln * x + 5 = 7 Multiply ln * x 4lnx + 5 = 7 Reorder the terms: 5 + 4lnx = 7 Solving 5 + 4lnx = 7 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 4lnx = 7 + -5 Combine like terms: 5 + -5 = 0 0 + 4lnx = 7 + -5 4lnx = 7 + -5 Combine like terms: 7 + -5 = 2 4lnx = 2 Divide each side by '4nx'. l = 0.5n-1x-1 Simplifying l = 0.5n-1x-1
| 14x+5=35 | | x^4-4x^3+6x^2-4x+1=0 | | 4a^2-22a+10=0 | | a-9=7+6 | | 33x+4y=-33 | | 5-.67(2k-1)=7 | | p+8=15+10 | | 5y^2-15y-140=0 | | 3z^2+54z+243=1 | | 73+t=101 | | 3x+4y=-33 | | 5x^2+8=383 | | 4x^2-9x+12=0 | | 75=k+11 | | c-19=22 | | X*x-x-182=0 | | q+23=31 | | -6.9(3x+5)-1.4(4x-6)= | | 5v^2-36v+36=0 | | 4x^3+1=0 | | 9x+12=21 | | 8x+y+2=-72 | | .4x^2-x-.75=0 | | 3x^2-24x-39=0 | | -3x^2-9x+11=0 | | 0.2x^2+3x-1.8=0 | | x^2-4x+4=6 | | 1x^2-3x-2=0 | | 81c-64c^3=0 | | X(2x+1)(x+1)=0 | | 2x+9-x=9+3x-6 | | 3x^2+3x-9=0 |